High-Performance Supercapacitors: A Comprehensive Review on Paradigm Shift of Conventional Energy Storage Devices - K. C. Seetha Lakshmi; Balaraman Vedhanarayanan (Batteries, 2023)
The enormous demand for energy due to rapid technological developments pushes mankind to the limits in the exploration of high-performance energy devices. Among the two major energy storage devices (capacitors and batteries), electrochemical capacitors (known as ‘Supercapacitors’) play a crucial role in the storage and supply of conserved energy from various sustainable sources. The high power density and the ultra-high cyclic stability are the attractive characteristics of supercapacitors. However, the low energy density is a major downside of them, which is also responsible for the extensive research in this field to help the charge storage capabilities thrive to their limits. Discoveries of electrical double-layer formation, pseudocapacitive and intercalation-type (battery-type) behaviors drastically improved the electrochemical performances of supercapacitors. The introduction of nanostructured active materials (carbon-/metal-/redox-active-polymer/metal-organic/covalent-organic framework-based electrode materials), electrolytes (conventional aqueous and unconventional systems) with superior electrochemical stability and unprecedented device architectures further boosted their charge storage characteristics. In addition, the detailed investigations of the various processes at the electrode–electrolyte interfaces enable us to reinforce the present techniques and the approaches toward high-performance and next-generation supercapacitors. In this review, the fundamental concepts of the supercapacitor device in terms of components, assembly, evaluation, charge storage mechanism, and advanced properties are comprehensively discussed with representative examples.